Disability in amyotrophic lateral sclerosis compared with traumatic brain injury using the World Health Organization Disability Assessment Schedule 2.0 and the International Classification of Functioning minimal generic set. Issue 3 (September 2018) - Tarvonen-Schröder, Sinikka; Kaljonen, Anne; Laimi, Katri
Abstract : We compared the functioning of two neurological patient groups, amyotrophic lateral sclerosis (ALS) and traumatic brain injury (TBI), using brief and validated International Classification of Functioning (ICF)-based tools. A 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0) questionnaire was mailed to ALS and TBI patients and their significant others 2 weeks before their appointment at an outpatient clinic of a university hospital. In addition, a neurologist filled in the ICF minimal generic set. Two years after diagnosis, no significant differences between the two diagnosis groups were found in overall functioning or in working ability using either patient or proxy WHODAS or physician-rated minimal generic set. In single items, however, clear differences were found. Patients and significant others rated household activities, mobility, and self-care as more impaired in the group with ALS, and learning, concentrating, and maintaining friendships in the group with TBI. There were no differences between the two diagnosis groups in the WHODAS items emotional functions, engaging in community, relating with strangers, or in working ability. Both brief ICF-based generic scales, WHODAS and the ICF generic set, could show differences between these patient groups with severe disability. The results of this study should promote assessment of disability with WHODAS 2.0 in ALS and TBI.